Geotechnical properties of the Singapore marine clay - Lim, Thian Loke; Prinzl, Frediric; Balasubramaniam, A.S.; Yudhbir; Government of The United States of America (Bangkok : Asian Institute of Technology, 1982)
This study is aimed at collecting , as much as possible, available borehole records and laboratory tests results on the Singapore marine clay, and then analyzing them. Soil investigation data had been a collected from government departments and private soil investigation firms in Singapore. A review of the geology of Singapore is presented, with emphasis on the Marine Member of the Kallang Formation. Some typical borehole profiles found in the marine clay areas are shown and an isopach map of the marine clay for the city of Singapore is produced. The microstructure of the Singapore marine clay is briefly reviewed. Based on the collected data, the study on the geotechnical properties of the Singapore marine clay include its index properties, shear strength characteristics and compressibility characteristics. Typical ranges of values of its geotechnical properties are presented. Correlations between the various soil parameters such as shear strength and in-situ effective overburden pressure, compression index and water content, etc., are determined. Studies by other researchers on the Singapore marine clay are presented. Comparisons are made between the Singapore marine clay and the other marine clays of the world, especially those in South East Asia. An experimental investigation was carried out to construct a sedimentation compression curve for the Singapore marine clay.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M. Eng.) - Asian Institute of Technology, 1982
Keywords: Clay -- Singapore -- Testing